Unraveling the genetic basis of schizophrenia with SNP as a potential genetic marker: a systematic review - Azman, Norainin Sofiya; Abd. Rahim, Nour El Huda; Mat Rasid, Siti Norain; A.Talib, Norlelawati; Abdull Jalil, Mohd Asyraf; Md. Rosli, Ahmad Nabil (2023)
Schizophrenia is a psychiatric disorder that is known for its complexity and genetic heterogeneity. Researchers have been working diligently to identify single nucleotide polymorphisms (SNP) that are linked to schizophrenia. These SNPs can serve as genetic markers that help us understand the underlying genetic architecture and pathogenesis of the disease. Recent research has focused heavily on SNPs in schizophrenia, and the findings have been promising. Thus, this systematic review provides valuable insights into the SNPs associated with schizophrenia and their potential use as genetic markers for unraveling the genetic basis of this disorder. To conduct this review, we searched databases such as PubMed, SCOPUS, ScienceDirect, and ResearchGate for English-language articles published between 2000 and 2023. We used specific keywords such as "single nucleotide polymorphism," "genetic markers," "schizophrenia," and "genomic" and limited our search to the subject areas of Biochemistry, Genetics, and Molecular Biology. After a thorough review, we included 23 relevant articles in our analysis. Our review revealed strong evidence that SNPs in various genes such as ANKK1, LTA, C3, C4, C4A, HHAT, GRM3, DRD2, PDE4B, COMT, RELN, IMPA2, VRK2, DAO, DNMT1, TNFR2, SOX11, AHI1, MBD2, CACNA1l, CHRNA5, and NOTCH4 are associated with an increased risk of schizophrenia in different populations. The discovery of these findings suggests that SNP could serve as a possible genetic marker for schizophrenia. In addition to blood samples, saliva samples were also used to extract genomic DNA. Furthermore, various SNP genotyping detection methods were used throughout the studies. Emerging technologies such as next-generation sequencing hold promise for improving the efficiency and accuracy of SNP detection, as they enable high-throughput and comprehensive analysis of SNPs as well as allow for the simultaneous detection of many SNPs. Overall, SNPs can potentially serve as genetic markers for schizophrenia, providing researchers with more comprehensive genetic information to unravel the genetic architecture and pathogenesis of this disease.